Fuchs’ endothelial corneal dystrophy: a controlled prospective study on visual recovery after endothelial keratoplasty - Nielsen, Esben; Ivarsen, Anders; Kristensen, Simon; Hjortdal, Jesper (Acta ophthalmologica (Oxford, England), 2016)
Purpose To investigate the determining factors of vision and subjective outcome after Descemet's stripping automated endothelial keratoplasty (DSAEK) for Fuchs’ endothelial dystrophy (FECD). Methods In a prospective study, 41 FECD patients who received DSAEK were compared to 40 cataract patients with normal corneas who received cataract surgery (control group). Subjects were recruited between March 2013 and July 2014. Observational procedures included the following: best‐corrected visual acuity (BCVA), contrast sensitivity (CS), Catquest‐9SF questionnaire, Scheimpflug tomography and anterior OCT. Examinations were carried out before surgery and at 3‐, 6‐ and 12‐month follow‐up. Main outcome measures were associations between corneal optics and visual parameters, as well as subjective improvement (Catquest‐9SF effect size) Results Best‐corrected visual acuity (BCVA) negatively correlated with anterior higher‐order aberrations (HOA's) (p < 0.001) and central corneal thickness (p = 0.001). Contrast sensitivity (CS) was negatively correlated with anterior HOA's (p = 0.002) and positively correlated with posterior densitometry (p = 0.008). Catquest‐9SF effect size was 1.32 (CI: 1.0–1.6) in the control group, 1.84 (CI: 1.4–2.3) in FECD patients who received phacoemulsification and intra‐ocular lens implantation in combination with DSAEK (n = 26) and 1.37 (CI: 0.6–2.1) in pseudophakic FECD patients who received DSAEK (n = 15). Conclusions DSAEK surgery leads to considerable improvement in patient‐reported outcome in FECD patients. There was a strong correlation between anterior HOA's and vision after DSAEK, suggesting that anterior corneal pathology constitutes the major limitation for visual recovery after DSAEK.